Education on Prevention of Transmission of ARI in Toddlers during the Covid-19 Pandemic - siwi, Ignasia Nila Siwi (ABDIMAS Madani, 2021)
The COVID-19 pandemic is still engulfing the world today. The number of morbidity and mortality due to COVID-19 is increasing every day. ARI is one of the symptoms that show Covid-19. Almost every toddler experiences ARI in life. Toddlers who are placed in child care have a high risk of transmitting and contracting ARI. Community service activities aim to provide education on Prevention of Transmission of ARI in Toddler Children During the Covid-19 Pandemic so that preventive thinking can be achieved. The method used in this community service activity is interactive lectures and discussions. This community service activity resulted in four discussions, namely how to deal with colds that don't go away, how to measure the dose of paracetamol for babies aged 1 year, if the drug is bought from a pharmacy, natural cough medicine for babies 1 year and over and cough cold treatment for babies 1 year old. down. Keywords: ARI, Toddler, Covid-19